Islamic Populism and The Ideology of the Front Islamic Defender (Front Pembela Islam) in Indonesia - Sait Abdullah; Abdul Rahman; Muhammad Naem Aziz (CV. Media Digital Publikasi Indonesia, 2025)
Islamic populism as part of contemporary political dynamics in Indonesia is unlikely to ever subside even though Indonesia was hit by the Covid 19 outbreak. In the context of power contestation, many scholars have argued that Islamic populism in Indonesia plays a very important role in supporting the elite to mobilize the masses and gain support for their political legitimacy. However, there is limited study to explain the role of ideology the FPI as social agent of Islamic populism. The study exemplifies the role of ideology of the Front Islamic Defender reflecting in the idea of ‘amar maruf nahi mungkar’ in current development of Islamic politics in Indonesia. By using a structural political economy approach, the author argues that although the formal organisation of the FPI has been dismantled by the Indonesian governement, yet the Islamic populism as a contested idea that has strong historical roots will continue to exist and develop if the contestation for power continues. As a political ideology that has a strong social and material basis, ‘amaruf nahi mungkar’ will still exist and become the ideological basis that supports the legitimacy of political elites in the contest for power and resources.